Review of electro-active shape-memory polymer composite - Liu, Yanju; Lv, Haibao; Lan, Xin; Leng, Jinsong; Du, Shanyi (Composites science and technology, 2009)
Shape-memory polymers (SMPs) have been one of the most popular subjects under intensive investigation in recent years, due to their many novel properties and great potential. These so-called SMPs by far surpass shape-memory alloys and shape-memory ceramics in many properties, e.g., easy manufacture, programming, high shape recovery ratio and low cost, and so on. However, they have not fully reached their technological potential, largely due to that the actuation of shape recovery in thermal-responsive SMPs is normally only driven by external heat. Thus, electro-activate SMP has been figured out and its significance is increasing in years to come. This review focuses on the progress of electro-activate SMP composites. Special emphases are given on the filler types that affect the conductive properties of these composites. Then, the mechanisms of electric conduction are addressed.